Recycle of sugarcane molasses by Aurantiochytrium sp. for high-value docosahexaenoic acid - Wang, Qing; Jin, Wenbiao; Qin, Yujia; Zhou, Xu; Chen, Yidi; Sun, Jing; Ansar, Sabah; Jiang, Guangming (Biotechnology and bioprocess engineering, 2024)
Sugarcane molasses is one of the by-products from the sugar industry, which is a candidate carbon source for microbes to produce high-value docosahexaenoic acid (DHA) that is beneficial to human health. The aim of this study was to optimize the sugarcane molasses medium for DHA production by Aurantiochytrium sp. and investigate the treatment and disposal of sugarcane molasses fermentation wastewater. Firstly, the sugarcane molasses volume ratio, carbon–nitrogen ratio and citric acid concentration were optimized for the sugarcane molasses medium, and the DHA production in Aurantiochytrium sp. R2A35 was increased from 2.63 to 7.48 g/L. Then, the two-staged oxygen supply strategy was adopted in the expanded culture, and the DHA production reached to 10.04 g/L. And the DHA proportion in total lipid was significantly improved from 41.08 to 60.46% (w/w), which promoted the total DHA production. The data showed that high oxygen supply promoted biomass accumulation and low oxygen supply promoted DHA accumulation in Aurantiochytrium sp. R2A35. It was also found that Aurantiochytrium sp. R2A35 preferred to use the reducing sugar in sugarcane molasses and then used sucrose. The final utilization rate of reducing sugar was 100% and the utilization rate of sucrose was 94.37%. Finally, the concentrated fermentation wastewater, sugarcane leaves and bagasse were mixed as a ratio of 2:5:12 for composting, and the compost product could meet the commercial organic fertilizer standard. This study accelerated the resource utilization of sugarcane waste and provided an alternative solution for DHA industry.